How Hyper-Personalization Shapes Satisfaction, Trust, and Loyalty: A Study of E-Commerce and Social Commerce - I Putu Bagus Arya Githa Wibawa; Agus Fredy Maradona (Green Publisher Indonesia, 2026)
Rapid growth in e-commerce and social commerce platforms has encouraged businesses to implement strategies that enhance customer experience and strengthen consumer loyalty. This research investigates how Value Co-Creation Behaviour and AI-Driven Personalization influence Trust, Brand Experience, Attitude, Satisfaction, Purchase Intention, and Loyalty among users of e-commerce and social commerce platforms in Indonesia. This study integrates Value Co-Creation Behaviour and AI-Driven Personalization into a unified model to explain the formation of customer loyalty. A quantitative approach was employed, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study involved 405 active Indonesian users of social commerce and e-commerce platforms selected through purposive sampling. The results show that Value Co-Creation Behaviour and AI-Driven Personalization have significant and positive effects on Brand Experience and Trust. However, Value Co-Creation Behaviour does not have a direct influence on Attitude and Satisfaction. Trust has a significant and positive effect on Purchase Intention and Loyalty, while Attitude has a significant and positive effect on Purchase Intention. Furthermore, Purchase Intention positively influences Purchase Behavior, which subsequently enhances Satisfaction and Loyalty. These findings suggest that integrating AI-Driven Personalization and Value Co-Creation Behaviour into a hyper-personalization strategy can enhance customer experience and foster consumer loyalty on e-commerce and social commerce platforms.